Studies on properties of Simarouba glauca fruit and kernel relevant to mechanical decortication - A. K. DASH; P.K. SAHOO; L.M. DAS; S.N. ΝΑΙΚ (Seed Research, 2026)
The high non-edible oil content in the Simarouba glauca DC. kernel makes it an appropriate candidate for production of biodiesel. Mechanical decortication is a need based operation for mass production of biodiesel from Simarouba glauca fruit. The properties of Simarouba glauca fruit and kernel namely, dimensions, 1000 unit mass, fruit part fraction, arithmetic mean diameter, geometric mean diameter, surface area, sphericity, aspect ratio, bulk density, true density, porosity and angle of repose were studied. The kernel has 8.51% (w.b.) moisture and 61.04% oil content which was higher than the fruit and shell. The average fruit length, width, thickness and 1000 unit mass were 21.26 mm, 13.81 mm, 11.03 mm and 1120.16 g while the corresponding value for kernel are 13.78 mm, 7.77 mm, 6.71 mm and 330.26 g respectively. The sphericity and surface area of fruit were 5.8% and 63.36% more respectively than that of kernel. Bulk densities of fruits and kernels were 622.27 and 727.73 kg/m³ and the corresponding true densities were 931.96 and 1019.3 kg/m³ respectively. The porosities of fruits and kernels were 33.23% and 28.61% respectively. The angle of repose of fruit and kernel were 31.35° and 35.02° respectively. The static coefficient friction for simarouba fruit was 31-39% higher than the kernel for different surfaces tested. On the basis of this study, design values for different parameters relevant to mechanical decortications were selected.